The Role of Renewable Energy Sources in Energy Production and Use - Csipkés , Margit (International Journal of Engineering and Management Sciences, 2020)
The role of renewable energies in energy management is growing both in the European Union and in Hungary. The use of renewable energy sources is already quite large (transport, heating, lighting, etc.) and it is advisable to deal with these energy sources in the year 2020. The use of energy from renewable sources can reduce greenhouse gas emissions and reduce dependency on the continuously problematic oil and gas market. A review of energy data over the last 10 years shows that renewable energy sources are playing an increasingly important role in the European Union. I support this finding by the fact that the share of energy from renewable sources in gross energy consumption has almost doubled in the last few years.